Occurrence of Accessory Mental Foramen - ELANGKOVAN, DENESH RAJ; GANAPATHY, DHANRAJ (The journal of contemporary issues in business and government, 2020)
The mental foramen is an oval or circular opening on the anterior surface of the mandible. Mental foramen is the determinant of the mental triangle and forms an important landmark of the human mandible. Mental nerves and vessels pass through it and supply the area from canine to first molar. The mental nerve is the neurosensory nerve. Mental Foramen it’s important landmark and orientation which serves surgical, local anaesthetic and other invasive procedures for oral and maxillofacial surgery. Understanding the anatomy of this region is important for effective nerve block and to avoid neurovascular bundles. It is also important to identify the ideal location of mental foramen for periodontal surgery, flap operation of lower tooth and for orthodontic surgery. Even so, in order to avoid neurovascular complications, particular attention should be paid to the possible occurrence of one or more accessory mental foramen during surgical procedures involving the mandible. The mental foramen is an important structure that needs to be considered in the surgery.